HASIL BELAJAR MATEMATIKA SISWA DENGAN MODEL PEMBELAJARAN STAD MELALUI PENDEKATAN PEMBELAJARAN BRAIN BASED LEARNING - ., Hidayatulloh (JURNAL E-DUMATH, 2016)
This research aims to improve the average of the students achievement in math atSMP Tri Sukses Natar Lampung Selatan in the academic year 2014-2015 byapplying STAD cooperative learning model by using brain based learningapproach in square material. This research used experimental method. Thepopulation was all of the first grade students at SMP Tri Sukses Natar LampungSelatan in the academic year 2014-2015. The samples of the research were takenby using the cluster random sampling technique. The result of the research canbe concluded that the average of the students achievement in math that wastreated by applying STAD cooperative learning model by using brain basedlearning approach in square material was higher than the average of thestudents achievements in math was treated by applying STAD cooperativelearning model by using contextual teaching learning approach.Keywords: STAD cooperative learning model, brain based learning approach,contextual teaching learning approach